Sustainable Agriculture and Ecological Construction in Rural Economic Development - Fu, Jin (Journal of Theory and Practice of Management Science, 2024)
Agriculture is an important part of economic development. Plant industry is an important part of national food security. the agricultural economy is very rich: it includes not only crops, livestock and forestry related to large-scale agriculture, but also non-agricultural industries. In many areas, agriculture is the backbone of the rural economy. Lack of ideas in the development process, whether in agriculture or industry, will have a certain impact, even damage the ecological landscape. It has become an important factor hindering the development of rural society in the world. the destruction of rural ecological environment has become one of the obstacles to agricultural development. At the Labor Conference held in December 2014, the CPC Central Committee stressed the need to further accelerate the process of agricultural transformation, focus on quantity, quality and efficiency, improve competitiveness as soon as possible, innovate agricultural technologies, and realize the sustainable and effective development of modern agriculture..